The Process and Problems of EFL Learners in English Writing - Muamaroh Muamaroh; Vira Cahya Mukti; Dwi Haryanti (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The objectives of the study were to investigate the process of English writing from students of undergraduate international class, to describe problems faced by students in writing English, and to find out the factors which inhibit and improve their writing skills. There were six female respondents in international class. The study used documentation from the students’ work, open-ended questionnaire and interview as the instruments for data gathering. All the data were analyzed by using descriptive qualitative approach. The results of this study showed that all students used four stages in the process of English writing: planning, drafting, editing and final revision. The students’ English writing problems covered content, organization, vocabulary, language use and mechanic. The factors which inhibit them in writing English included not being confident in writing English, not mastering grammar and vocabulary, and lack of practice in writing. The aspects which encourage them to write English were due to the demands as international class students, watching English movie, reading English books or journals, listening English songs and having ambition to acquire scholarship overseas.